Medical negligence in Bangladesh: A quest for feasible reform - Uddin, Mohi (IIUC Studies, 2022)
The term "Medical Negligence" is an issue of grave human rights apprehension that directly affects the "right to life and right to health care" which also the concern for all parties involved in medical care facilities. Most State-sponsored have passed Acts and established courts to fortify health care laws. Though there are no precise and inclusive laws to stop "medical negligence" in Bangladesh, various legal mechanisms are still in place under different laws that are not specifically codified. As a result, the possibility of medical-based legal consequences remains out of the orbits of courts, and leads to violence, which invites many complications. However, hospital malpractices cause sufferings and unnecessary deaths for numerous people. There is no denying fact that people suffer and occasionally die due to reckless medical treatment in our country. This article will describe the legal sphere of medical negligence, evaluate the present laws on "medical negligence" in Bangladesh, and emphasize the quest for feasible reform to elevate this unaddressed legal pitch for the benefit of the people. IIUC Studies Vol.18, December 2021: 157-172